MATHEMATICAL MODELING OF THE GRAIN MATERIAL SEPARATION IN THE PNEUMATIC SYSTEM OF THE GRAIN-CLEANING MACHINE - Badretdinov, Ildar; Mudarisov, Salavat; Tuktarov, Marat; Dick, Elizabeth; Arslanbekova, Svetlana (Journal of Applied Engineering Science, 2019)
The article presents the results of a study of a high-performance grain cleaning machine for the preliminary cleaning of grain pile with a closed aspiration system. The flow regimes of the “air-grain pile” mixture determined by the Reynolds number and the bulk concentration of particles are established. As a result of the modeling, further directions for improving pneumatic systems of grain cleaning machines were determined: the cleaning efficiency of the Е0 fraction of pure grain from light impurities, shriveled and crushed grain reaches 82%, the output cleanliness of the grain was 93.7%, and the loss of full grain to waste Pz = 0,017%. The average speed of the air flow in the separating channel is U = 7.12 m / s, its coefficient of variation across the width of the separating channel is v = 12,7%. The results of the experimental data confirmed the adequacy of using mathematical modeling of the air flow in the pneumatic system of a grain cleaning machine to substantiate the basic parameters of the pneumatic system.
Keywords: process modeling; grain pile separation; pneumatic system; grain cleaning machine; Mathematical Model